Fourth World Peoples: Continuity, Philosophies, and Sources (Fourth World Journal, 2025)
This essay establishes a critical inspection of the notion of Fourth World as it pertains to its continuity in terms of historicity and cultural presence in the Americas. In doing so it argues that such a historicity is to be found first and foremost in prioritizing an until recently much neglected, account of Fourth World Peoples’ sources of writings and cultural records. Recent exploration into these records has led to new critical ventures that open new dimensions in the narratives of intercultural encounter from the past five hundred years between America and Europe. A dimension that Brotherston surmises echoing the words of the early Mesoamerican historiographer, Chimalpahin in response to the European conquerors, “Who entered whose history?” Such inspection, the essay argues, allows us to hisotricize a narrative of social, economic, ecological and cultural diversity and richness that critically contributes to current modes of sustainability and models of production in late capitalist societies.